Hesperidin Inhibits Lung Cancer In Vitro and In Vivo Through PinX1 - Yao, Yang; Lin, Mingyue; Liu, Zhujun; Liu, Mengyang; Zhang, Shiheng; Zhang, Yukun (Frontiers in Pharmacology, 2022)
Graphical Abstract